Coinfección de mucormicosis rinocerebral y aspergilosis sinusal - Torres Damas, William (2016)
Mucormycosis and aspergillosis are the most frequent fungal infections caused by filamentous fungi; coinfection in the same host is rare. We present a case of a 78-year-old male patient with the debut of type 2 diabetes mellitus and ketoacidosis, with swelling of the right side of the face, right facial paralysis, ptosis and a necrotic ulcer in the right palate. Facial Computed tomography showed an abscess of the right maxillary sinus. Cultured secretions revealed Aspergillus fumigatus. The pathology result of biopsies of the palate, maxillary sinus and ethmoid bone was consistent with mucormycosis. The patient was treated with voriconazole, amphotericin B deoxycholate, and surgical debridement of the maxillary sinus. The patient died despite the treatment. The coinfection of Rhinocerebral mucormycosis and aspergillosis should be suspected in immunosuppressed patients in order to establish early management that can permit an improved prognosis of the disease.